MEWUJUDKAN ISLAM MODERAT MELALUI PENDIDIKAN AGAMA DI SMK HIDAYATUL MUBTADI'IEN BALEN BOJONEGORO - AMIRUDDIN, AMIRUDDIN; MAKINUDDIN, MOHAMMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Millennial generations need to have a deeper understanding of religious moderation from an early age so that they develop polite attitudes, such as harmony, mutual respect, appreciation, and the willingness to accept differences. Therefore, the background of this thesis highlights the importance of internalizing the values of moderate Islam in Islamic Religious Education (PAI) at SMK Hidayatul Mubtadi'ien Balen Bojonegoro. The research questions addressed in this study are: 1) How is the process of internalizing the values of moderate Islam in PAI learning at SMK Hidayatul Mubtadi'ien Balen Bojonegoro? 2) What are the supporting and inhibiting factors for internalizing the values of moderate Islam in PAI learning at SMK Hidayatul Mubtadi'ien Balen Bojonegoro? 3) What are the implications of internalizing the values of moderate Islam in PAI learning at SMK Hidayatul Mubtadi'ien Balen Bojonegoro ? This research uses a descriptive qualitative approach, with data analysis employing Data Collection, Data Reduction, Data Display, and Conclusion Drawing/Verification, so that the data obtained will result in descriptive and natural data. The data collection techniques include interviews, observations, and documentation, while data validity is ensured through Credibility Testing, Transferability Testing, and Dependability Testing. The research findings show that: A) The process of internalizing the values of moderate Islam in PAI learning at SMK Hidayatul Mubtadi'ien Balen Bojonegoro includes the stages of Value Transformation, Value Transaction, and Transinternalization. B) The supporting and inhibiting factors for internalizing the values of moderate Islam in PAI learning at SMK Hidayatul Mubtadi'ien Balen Bojonegoro are as follows: a) Supporting factors include: high commitment from human resources and adequate facilities, active extracurricular activities, and competent educators. b) Inhibiting factors include: the influence of social media and the lack of literacy materials. C) The implications of internalizing the values of moderate Islam in PAI learning at SMK Hidayatul Mubtadi'ien Balen Bojonegoro include: obedience, respect for others, closeness with friends and teachers, and social care. ABSTRAKGenerasi milenial perlu memiliki pemahaman yang lebih mendalam tentang moderasi beragama sejak dini agar mereka memiliki sikap santun, seperti kerukunan, saling menghormati, menghargai, dan mau menerima perbedaan. oleh karena itu latar belakang artikel ini mengemukakan pentingnya internalisasi nilai-nilai ajaran Islam moderat dalam pembelajaran Pendidikan Agama Islam (PAI) di SMK Hidayatul Mubtadi'ien Balen Bojonegoro. Adapun permasalahan yang dikaji adalah: 1). Bagaimana proses internalisasi nilai-nilai Islam moderat dalam pembelajaran PAI di SMK Hidayatul Mubtadi'ien Balen Bojonegoro? 2). Apa saja faktor pendukung dan penghambat internalisasi nilai-nilai islam moderat dalam pembelajaran PAI di SMK Hidayatul Mubtadi'ien Balen Bojonegoro? 3). Bagaimana implikasi dari internalisasi nilai-nilai islam moderat dalam pembelajaran PAI di SMK Hidayatul Mubtadi'ien Balen Bojonegoro? Penelitian ini menggunakan Pendekatan Kualitatif Deskriptif, dengan analisis data menggunakan Data Collection, Data Reduction, Data Display, Conclusion Drawing/Verification, sehingga data-data yang diperoleh akan menghasilkan data-data deskriptif yang bersifat alamiah, adapun teknik pengumpulan data nya menggunakan wawancara, observasi dan dokumentasi, untuk keabsahan data menggunakan Uji Kredibilitas, Pengujian Transferability, Pengujian Dependability. Hasil penelitian menunjukkan bahwa; A). Proses Internalisasi Nilai-Nilai Islam Moderat Dalam Pembelajaran PAI di SMK Hidayatul Mubtadi’ien Balen Bojonegoro yakni Tahap Transformasi Nilai, Tahap Transaksi Nilai, Tahap Transinternalisasi. B). Faktor pendukung dan penghambat Internalisasi Nilai-Nilai Islam Moderat Dalam Pembelajaran Pendidikan Agama Islam di SMK Hidayatul Mubtadi'ien Balen Bojonegoro a). Faktor Pendukung diantaranya: Komitmen yang tinggi dari SDM dan fasilitas yang memadai, Adanya kegiatan ekstrakurikuler yang aktif, Pendidik yang kompeten. b). Faktor penghambat diantaranya: Faktor media sosial, Kurangnya Bahan Literasi. C). Implikasi Internalisasi Nilai-Nilai Islam Moderat dalam Pembelajaran Pendidikan Agama Islam di SMK Hidayatul Mubtadi’ien Balen Bojonegoro. Yakni Taat, Menghormati orang lain, Keakraban dengan teman dan guru, Kepedulian sosial.